The Non-Monetary Effects of Education on Leisure: Analysis of the Use of Time in Spain - Marcos Fernández-Gutiérrez; Jorge Calero (Universidad de Navarra, 2019)
The analysis of the effects of education have traditionally focused on income (the monetary effects), whilst other non-monetary effects of education (such as those on the use of time), have received less attention. This paper analyses the effects of education on individuals' use of their leisure time in Spain, using data from the Spanish Time Use Survey. It fi nds a close relation between education and the dedication of time to cultural activities, sports and reading books and the press. It also fi nds that a higher educational attainment does not automatically increase participation in all the leisure activities considered as benefi cial. The effects, according to an institutionalist perspective, will be derived from social environment and individual's values.